Exploring the effects of long-term physical exercise on persistent and inhibitory self-control: quasi-experimental research - Cheng, Linjing; Qin, Huahui; Yang, Yin; Dang, Junhua (Frontiers in Sports and Active Living, 2025)
This study aims to explore the effects of long-term physical exercise on different types of self-control, with a focus on persistent and inhibitory self-control. Two experiments were conducted using dual-task paradigms. In Experiment 1, the E-crossing task served as the depletion task, and the grip task was used to measure persistent self-control. Results indicated that long-term exercisers exhibited significantly better persistent self-control than non-exercisers, F(1, 54) = 6.55, p = .013, ηp2 = 0.11. Experiment 2 employed the Stroop task as the detection task to measure inhibitory self-control. No significant differences were found between the exercise and non-exercise groups in inhibitory self-control performance. These findings suggest that long-term physical exercise may enhance persistent self-control, but its effects on inhibitory self-control remain unclear. The study addresses potential confounding factors, such as task-specific effects and baseline performance differences, and highlights the need for future research to explore diverse self-control tasks and establish causal relationships. The results contribute to the understanding of self-control training and provide insights into the domain-specific effects of physical exercise on self-control.